Facile synthesis of palladium incorporated NiCo₂O₄ spinel for low temperature methane combustion : activate lattice oxygen to promote activity - Wang, Ting (2022)
While palladium-based catalysts are effective in low-temperature methane combustion, their high cost and scarcity render them unsuitable to fulfil the growing demand. The design of improved catalysts which can more efficiently utilize this precious metal is required. Here, by using a facile one-pot thermal decomposition method Pd-NiCo2O4 spinel catalysts with a unique structure are obtained, in which the majority of Pd incorporated into the bulk spinel structure of NiCo2O4 with limited highly dispersed PdOx species on the surface at an atomic scale. The robust 1 %Pd-NiCo2O4 spinel catalyst exhibits comparable activity in methane oxidation to that of the conventional incipient wetness impregnation 2 %Pd/NiCo2O4. Theoretical calculations and catalyst characterizations (SEM, HRTEM, XRD, XPS, XAS, ICP-OES, etc.) revealed that the enhanced activity is mainly originated from having the O p-band center closer to the Fermi level, with Pd ions incorporated into the bulk NiCo2O4 via substituting for the octahedral coordinated Ni3+/Co3+.